Emission mechanism and wide-angle adaptability of selective emitter based on combination of one and two-dimensional photonic crystals - Cao, Shaowen; Cai, Qilin; Zhang, Yingshi; Zhang, Qi; Ye, Qing; Deng, Weifeng; Wu, Xi (Frontiers in Energy Research, 2023)
In this paper, a thermophotovoltaic (TPV) emitter that combines a one-dimensional photonic crystal with two-dimensional periodic nanoarray cavities was proposed. The Finite-Difference Time-Domain (FDTD) method was adopted to analyze the spectral emittance and its sensitivity to the emission angle for the proposed emitter. The results show that the main emission mechanisms of the emitter are Cavity Resonances (CRs), Fabry-Perot (FP) resonances, and Magnetic polaritons (MPs). In the convertible band of a TPV cell, CRs and FP resonances are coupled together to broaden the emitting bandwidth of the emitter. The cut-off wavelength of structural spectral emittance increases with depth and radius but decreases with a period. In addition, the spectral emittance is non-sensitive to the emission angle of less than 50°, highlighting the wide-angle stability of the composite structure. The proposed emitter has wide-angle adaptability and achieves a fine-tunning of bandgap wavelength while maintaining a good spectral selectivity. This work provides new insight into the design of the TPV emitter.